Food Insecurity, Population Growth, Urbanization and Water Availability: The Role of Government Stability - Shazia Kousar (MDPI AG, 2021)
To examine the impact of population growth, urbanization and water availability on food insecurity, this study utilized time series data for the period of 1990–2019, from World Development Indicators (WDI), Food and Agriculture Organization (FAO), and World Bank. The study applied an Auto-regressive distributive lag (ARDL) co-integration approach to test the hypothesized relationships among modeled variables. The study found a negative and significant association of water resources and agriculture research with food insecurity while urbanization and population growth has a significant and positive impact on food insecurity in the short-run as well as in the long-run period. Moreover, the study found that political stability has a negative and significant association with food insecurity in the short-run and long-run periods. Results also indicated that political stability significantly strengthens the relationship of water resources, and agriculture research with food insecurity while political stability weakens the relationship of urbanization and food insecurity significantly.